Tracer Study of the Nursing Graduates in a State College - Austria, Jayson S. (Future Science / FSH-PH Publications, 2023)
Introduction: This graduate tracer study aimed to improve the nursing program in a state college. Method: It used descriptive survey collect the nursing graduates' demographic, educational, and employment profiles, as well as their feedbacks. The study used 60% representative stratified and snowball samplings. Findings presented in frequency distribution tables. Feedbacks were grouped into themes. Results: The demographic profile showed varied age from 20 to 40 years old, who were largely female. The educational profile showed fluctuating nurse licensure examination percentage, and a large number who were not actively involved in continuing professional development. The employment profile showed a large number of graduates who were not employed in nursing related jobs and without permanent employment status. Conclusion: Thus, these findings corroborated the graduates' feedbacks that to produce quality graduates for the labor market, program offering improvement in terms of faculty, curriculum and instruction, library, and physical facilities is needed.